Team-based organizing - Beyerlein, Michael Martin; Johnson, D. A.; Beyerlein, Susan T. (Emerald, 2003)
Concluding the Advances in Interdisciplinary Studies of Work Teams series with a focus on team-based organizing, this title reveals how the context for teams is critical to their success. Environmental factors may determine team goal accomplishment more than factors internal to the team. In particular, alignment of support systems with work teams influences how well they can function and how the team members feel about reaching challenging goals. The initial chapter sets the stage for a context focus by describing the critical success factors that impact team environments and how to address those factors. The second chapter focuses on effective change practices for transforming organizations into effective collaborative systems. The third chapter examines the fit of support systems with teams, including management systems and culture. Chapter four ties these system pieces together in a model that translates the value of team process improvements into financial terms for strategic decision making. Other chapters focus on team level task analysis and organizational citizenship behaviour, including the complex flow of leadership in emergency room teams. As a whole, this volume presents a perspective on team practice and theory that should benefit a wide range of readers.
Keywords: Personnel management.; elektronické knihy; electronic books